Failure modeling of roof-truss supports of reinforced concrete frame residential buildings due to severe wind - Doguiles, Arvi Elijah R.; Tan, Liezl Raissa E.; Hernandez, Jaime Y. Jr. (Quezon City College of Engineering, University of the Philippines Diliman, 2015)
A failure model for the roof-truss supports had been developed using experimental data of resistances of bent reinforcing bar support and wind load estimation from computational fluid dynamics simulation. The methodology that was developed and used in the research was reliability-based modeling. The input parameters for the failure model include the house configuration and resistance of the supports. The failure model aims to assess the fragility of a structural component and obtain the probability of failure of the typical rooftruss support at different wind speeds and directions. Two random houses surveyed in Tacloban and Palo, Leyte with different dimensions and resistances were modeled for failure . Results show that for house 1 with 12mm diameter reinforcing bar support, the velocity at which at least one of the connections starts to fail is at around 95kph and the velocity at which all of the supports failed is at around 300kph. On the other hand, house 2 with 1Omm diameter reinforcing bar supports will most likely experience initial failure at around 140kph and total failure of the supports at around 260kph.
Thesis (B.S. Civil Engineering)--University of the Philippines Diliman
Keywords: Failure analysis (Engineering); Roof trusses